ENDOCRINE DISRUPTORS IN FEMALE FERTILITY - Anna Blazhkova; Magdalena Czaja; Martyna Łukaszyk; Hanna Sitka; Sven Solisch; Anna Susłow; Ewa Szczęsna (International Journal of Innovative Technologies in Social Science, 2025)
Introduction: Nowadays, the world is facing a global issue of infertility. Endocrine-disrupting chemicals (EDCs) influence homeostasis and contribute to the development of various diseases. The endocrine system plays a crucial role in maintaining proper body functions, including metabolism regulation, fluid and electrolyte balance, and, importantly, the regulation of reproductive functions. The EDCs analyzed in this study (pesticides, BPA, phthalates, parabens and phenols, and dioxins) are commonly found in everyday items such as food containers, personal care products, and even children’s articles. Recent studies show that their impact on the endocrine system contributes to female infertility. Purpose of the study: This study aims to investigate the relationship between EDCs found in everyday-use products and the female reproductive system, with an emphasis on their mode of action, substance-specific effects, and duration of exposure. Materials and methods: An overview of 31 articles sourced from PubMed and open-access databases was conducted. The reviewed literature focused on the disruption of follicular development, prolonged time to pregnancy, and reduced ovarian function. Most of the studies were conducted on women of reproductive age. Conclusions: EDCs have a negative impact on the female reproductive system on many levels, including hormonal regulation, cellular function, and gene expression.